REFLECTIONS ON THE CULTURAL DIVERSITY IN G. B. VICO (Andamios, Revista de Investigación Social, 2004)
In this paper there is a reflection about cultural diversity in G. B. Vico. The method used by this Neapolitan philosopher, emerges from the hermeneutic concept of fantasy, which together with common sense, make possible an integral and comprehensive relation. What some human beings fulfill can be understood by others even the complexities of puzzling out some different behaviors and languages. This is possible because our faculty of getting “the common”, understanding it as an imaginative penetration into those cultures, behaviors and languages. Language is the key to achieve the pretended communication among different cultural groups.